Outer synchronization between dynamic varying networks under noisy condition. Issue 3 (21st September 2018) - Liang, Hao; Sun, Yumei; Chi, Ronghu; Fang, Xinli; Wang, Jiaming
ABSTRACT: This paper exploits the outer synchronization between two dynamic networks with diversely varying node behaviours at the presence of noise. Aiming to obtain a generic technical solution for network outer synchronization, the problem is addressed for the dynamic network scenarios with non-identical topological structures, nonlinear inner coupling connections and time-delayed node characteristics. The impact of noise is fully considered in the theoretical and performance analysis which makes the derived synchronization criteria be able to be adopted in practical engineering deployment with minimized hurdles. By using a Lyapunov–Krasovskii energy function, the synchronization criteria and adaptive control solution are presented and the convergence of the system error states is also proved. Finally, the numerical analysis is carried out based on the simulation study and the result verifies the correctness and effectiveness of the suggested control solution.